From “Authoritarian Military Man” to “Hero of Oil Nationalism”. On the Political Uses of Mosconi in Contemporary Argentina - Carrizo, Gabriel Alejandro (Sociedad y Economía, 2012)
Recently, as a result of the so-called re-nationalization of oil promoted by President Cristina Fernandez de Kirchner, the figure of General Enrique Mosconi has become part of Argentina´s political discourse. In this article, first we’ll look at the construction of Mosconi as a hero of oil nationalism during the period of Military Government. Then we’ll discuss the political uses of his figure since the privatization of Yacimientos Petrolíferos Fiscales (YPF) to the current political context.